Conceptualizing the governance challenges for food system transformation - Vignola, Raffaele; Oosterveer, Peter (Frontiers in Sustainable Food Systems, 2025)
Approaches to food systems are receiving increased attention because they provide a more holistic perspective on the organization of food production and supply and on how to promote food safety, environmental sustainability, and equity. While the structure and complexity of food systems are widely acknowledged, efforts to understand their governance and possible challenges are just starting. We contribute to conceptualizing these challenges by harnessing the conceptual insights of multiple system governance frameworks. Conceptual and empirical lessons from these frameworks help to understand the possible challenges that may emerge when dealing with key features of modern globalized food systems. These include cross-spatial and temporal dynamics, managing common trade-offs across food system goals, and integrating narratives and policies when dealing with diverse stakeholders, sectors, and knowledge communities. We discuss the implications of addressing challenges that may arise in one or more of these key features, especially under the new governance paradigm in which modern food systems are embedded and in the presence of diverse paradigms and power asymmetries.